Review on Predictive Analytics for Student Performance Prediction - Vandana Bharadi, Dr. Madan Lal Saini (International Journal of Advanced Science and Technology, 2020)
In the developing country India, the retention rate of students at under-graduate and post-graduate level should be improved. The reasons for student’s failure and incapability of clearing examination with expected grades should be analyzed and the factors responsible for their failure should be worked upon. With the wider capabilities of predictive analytics, it can be made possible. Most importantly apart from only considering student’s academic records, all other socio-economic factors also to be studies effectively. These tasks will be carried out under the planned research work.